Classics of Public Administration - SHAFRITZ, Jay M (Thomson, 2004)
With this new seventh edition of CLASSICS OF PUBLIC ADMINISTRATION, authors Jay M. Shafritz and Albert C. Hyde aim to introduce students to the principles of public administration via the most significant scholarly writings on the topic. Straightforward and informative, this text begins its discussion with Woodrow Wilson and continues to today's political scientists. A new Section V, "Public Administration in a New Century," is dedicated to writing and thinking from the 21st century. This edition includes six new readings and addresses the key fields of public administration: bureaucracy, organization theory, human resources management, the budgetary process, public policy, implementation, evaluation, intergovernmental relations, and public service ethics.